ANALYSIS OF VISUAL ELEMENTS AND RESPONSES OF GENERATIONS Z ON INDOESKRIM ADVERTISING VIDEO - Igo Bani Christian; I Putu Mario Bintang Toti; I Made Candra Wiguna; Putu Chrisma Dewi; Putu Chris Susanto (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTAdvertisement is used to promote a product or service to the people and community.Video advertisement is primarily a choice as a media to promote these products. This studyaims to analyze one particular advertising media in a form of video used by Indofood icecream. Examining and analyzing the responses from the Indonesian Generation Z on thatadvertisement video using a descriptive qualitative approach. In addition to analysis of visualgrammar using the analysis tools by Kress and van Leeuwen, video elicitation interviewswere conducted with four participants to further explore the effectiveness of the visualelements from the perspective from generation Z. Using the hierarchy of effects model ofdetermining advertising effectiveness, paying close attention to the response on themeaningfulness of the visual advertising campaignKeywords : video advertising, visual elements, generation z, visual grammar, photoelicitation